2013
DOI: 10.1021/jp408111v
|View full text |Cite
|
Sign up to set email alerts
|

Transformations during Sintering of Small (Dcore < 2 nm) Ligand-Stabilized Gold Nanoparticles: Influence of Ligand Functionality and Core Size

Abstract: Ligand-stabilized gold nanoparticles have been investigated as both discrete entities with size-dependent properties and as precursor inks for low-temperature deposition of thin films and patterns. In the first instance it is important to preserve the nanoparticle core, whereas for thin film applications it is desirable for the nanoparticles to sinter at relatively low temperatures. In each case, a detailed understanding of the factors that govern nanoparticle sintering will lead to improved nanomaterial desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 72 publications
5
39
0
2
Order By: Relevance
“…4A) Taking into account the shape of the curve as well as the size of the synthesized nanoparticles the registered spectrum is in good agreement with the experimental results published previously [25,26]. The characteristic plasmonic band appears at around 500 nm, indicating a decrease in particle size [39].…”
Section: Uv-vis and Photoacoustic Spectrasupporting
confidence: 87%
See 2 more Smart Citations
“…4A) Taking into account the shape of the curve as well as the size of the synthesized nanoparticles the registered spectrum is in good agreement with the experimental results published previously [25,26]. The characteristic plasmonic band appears at around 500 nm, indicating a decrease in particle size [39].…”
Section: Uv-vis and Photoacoustic Spectrasupporting
confidence: 87%
“…On thiol protected small gold particles (1.5-5 nm range) the weight loss may amount to 15-35 wt% [19,25] depending on the molecular weight of the thiol molecules. The TG curve obtained on our sample is presented in Fig.…”
Section: Thermogravimetry and Xrd Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…80.76 %. TGA and DSC analysis of nanomaterials based on metallic nanoparticles are very commonly studied with respect to sintering nanoparticle inks for printed electronics [96][97][98][99][100]. Yu et al [99] presented TGA results and DSC profiles of AgNPs-organic molecules (in their case, the silver nanoparticles were obtained using sodium polyacrylate and ascorbic acid) with sizes of 20-30, 30-40 and 100-120 nm.…”
Section: Tga / Dsc Analysismentioning
confidence: 99%
“…The research of Smith and Hutchinson [100] indicated the dependency of the sintering process on the size of the nanoparticle and ligand shell. TGA revealed that the free ligand decomposed at lower temperatures in comparison with the ligand bound to the nanoparticle.…”
Section: Tga / Dsc Analysismentioning
confidence: 99%